LPTK Laboratory School Curriculum Management as Actualization of Independent Campus in Indonesia - Prayoga Bestari; Wahyu Sopandi; Rahman Mulyawan; Epin Saepudin (GoAcademica Research & Publishing, 2022)
This research focuses on curriculum management in the Laboratory Schools under the LPTK. Planning, actuating, and controlling are forms of curriculum management at the Labschool of Indonesian Education University (UPI), Ganesha Education University (UNDIKSHA), Padang State University (UNP), and Jakarta State University (UNJ). The method used is qualitative with purposive sampling. The subjects in this study were the principal, the head of the foundation/LPTK, teachers, and administrative staff. The results showed that curriculum management planning in each laboratory school was administratively implemented by a curriculum development team involving input from the LPTK. The implementation is fully in the control of the principal and vice principal in the field of curriculum, and a special team from the LPTK and foundations carries out supervision. This research is expected to provide an overview of curriculum management in laboratory schools and a reference for laboratory schools under the LPTK in Indonesia.